Infeksi Virus Dengue Tanpa Gejala pada Keluarga Penderita DBD di Provinsi Jawa Barat - Santya, Roy NRE; Riandi, M. Umar (Jurnal Biotek Medisiana Indonesia, 2012)
Dengue Hemorrhagic Fever (DHF) in Indonesia shows an increasing trend since it was first reported in 1968. Based on data from 2003 to 2007, all districts in West Java province had reported outbreak of DHF. Dengue virus transmission is kept up by the presence of virus in the infective host in human and/or mosquitoes. A cross-sectional research was conducted to obtain the incidence of asymptomatic dengue infections in family members of the individual infected. Data was extracted from respondents who were family members of patients that showed immunological response to dengue virus infection. Out of 979 family members of patients tested, 183 (18.7%) individual showed asymptomatic positive immunological response of dengue virus infection. Respondents who leave in a district have risk to be infected 1.35 fold greater than those who leave in a city (p= 0,043; 95% CI =1,004-1,805). There is no significant risk to be infected among gender (female and male respondent) and age groups (â¤ 15 years and > 15 years).There is a latent potential problem of sustainable dengue virus transmission in West Java Province. This condition requires attention because the existence of positive individuals without symptoms and their mobility play a role as a reservoir of dengue virus.Key words: dengue virus infection, asymptomatic, immunological responsesÂ AbstrakDemam Berdarah Dengue di Indonesia menunjukkan tren meningkat sejak dilaporkan sejak tahun 1968. Berdasarkan data tahun 2003-2007 seluruh Kabupaten di Jawa Barat melaporkan adanya KLB DBD. Transmisi virus dengue terus ada karena ada penularan virus antar manusia melalui nyamuk. Penelitian ini adalah Cross seksional yang dilakukan untuk mengetahui adanya insidens dengue tanpa gejala diantara anggota keluarga dari orang yang terinfeksi. Data diperoleh dari responden yang merupakan keluarga dari responden yang menunjukkan adanya respon imun terhadap virus dengue. Dari 979 anggota keluarga yang di test sebanyak 183 (18,7%) menunjukkan adanya respon imun terhadap virus dengue. Responden yang tinggal di kabupaten yang mempunyai risiko terinfeksi sebesar 1,35 lebih tinggi dari pada yang tinggal di dalam kota (p= 0,043; 95% CI = 1,004-1,805). Tidak ada risiko terinfeksi antara gender, kelompok umur (<15 tahun dan >15 tahun) yang signifikan. Terdapat problem laten untuk transmisi virus dengue yang terus menerus di Jawa Barat. Kondisi ini membutuhkan perhatian karena keberadaan individu tanpa gejala dan mobilitasnya berperan sebagai resevoa virus dengue.Kata kunci: Infeksi virus dengie, asymptomatic, respon imun